The European multistakeholder PanCareFollowUp project: novel, person-centred survivorship care to improve care quality, effectiveness, cost-effectiveness and accessibility for cancer survivors and caregivers. (August 2021) - van Kalsbeek, Rebecca J.; van der Pal, Helena J.H.; Hjorth, Lars; Winther, Jeanette F.; Michel, Gisela; Haupt, Riccardo; Uyttebroeck, Anne; O'Brien, Kylie; Kepakova, Katerina; Follin, Cecilia; Muraca, Monica; Kepak, Tomas; et al.
Abstract: Background: The majority of childhood cancer survivors are at risk of treatment-related adverse health outcomes. Survivorship care to mitigate these late effects is endorsed, but it is not available for many adult survivors of childhood cancer in Europe. The PanCareFollowUp project was initiated to improve their health and quality of life (QoL) by facilitating person-centred survivorship care. Methods: The PanCareFollowUp consortium was established in 2018, consisting of 14 project partners from ten European countries, including survivor representatives. The consortium will develop two PanCareFollowUp Interventions, including a person-centred guideline–based model of care (Care Intervention) and eHealth lifestyle coaching (Lifestyle Intervention). Their development will be informed by several qualitative studies and systematic reviews on barriers and facilitators for implementation and needs and preferences of healthcare providers (HCPs) and survivors. Implementation of the PanCareFollowUp Care Intervention as usual care will be evaluated prospectively among 800 survivors from Belgium, Czech Republic, Italy and Sweden for survivor empowerment, detection of adverse health conditions, satisfaction among survivors and HCPs, cost-effectiveness and feasibility. The feasibility of the PanCareFollowUp Lifestyle Intervention will be evaluated in the Netherlands among 60 survivors. Results: Replication manuals, allowing for replication of the PanCareFollowUp Care and Lifestyle Intervention, will be published and made freely available after the project. Moreover, results of the corresponding studies are expected within the next five years. Conclusions: The PanCareFollowUp project is a novel European collaboration aiming to improve the health and QoL of all survivors across Europe by developing and prospectively evaluating the person-centred PanCareFollowUp Care and Lifestyle Interventions. Highlights: Survivorship care may improve survivors' health and quality of life. Many adult childhood cancer survivors do not receive optimal survivorship care. PanCareFollowUp facilitates the implementation of survivorship care across Europe. Harmonised recommendations for long-term follow-up care will be developed. Models for survivorship care and lifestyle coaching will be developed and evaluated.